Simple Clinical Test to Detect Deltoid Muscle Dysfunction Causing Weakness of Abduction—“Akimbo” Test - Fujihara, Yuki; Doi, Kazuteru; Dodakundi, Chaitanya; Hattori, Yasunori; Sakamoto, Soutetsu; Takagi, Takehiko (Journal of Reconstructive Microsurgery, 2012)
Introduction Full range of motion and powerful shoulder abduction can be performed without any deltoid muscle function by the supplemental action of the supraspinatus and biceps brachii muscles. For evaluation of deltoid muscle function, we need to negate these actions, which can be done with the “akimbo test,” in which patients place their hands on the iliac crest with abduction in the coronal plane and internal rotation of the shoulder joint while simultaneously flexing the elbow joint and pronating the forearm.Methods We examined the akimbo test in five patients with incomplete upper-type brachial plexus injury, five patients with suprascapular nerve palsy, and six patients with axillary nerve palsy. Presence of some abduction is a prerequisite to perform this test.Results No patient with incomplete upper-type brachial plexus injury could demonstrate this sign when the deltoid did not show a certain level of the power to abduct the shoulder joint. All patients with suprascapular nerve could demonstrate this sign as the deltoid was normal. No patient with axillary nerve paralysis could demonstrate this sign.Conclusion The akimbo test is a simple clinical test to determine deltoid muscle paralysis or dysfunction, especially when patients can demonstrate shoulder abduction due to supplementary action of other muscles.
Keywords: axillary nerve paralysis; akimbo test; diagnosis